PENGARUH GAME BASED LEARNING MATA PELAJARAN INFORMATIKA KURIKULUM MERDEKA TERHADAP MOTIVASI DAN PRESTASI BELAJAR - Monalisa Monalisa (Padma Sari: Jurnal Ilmu Pendidikan, 2023)
The research aims to determine the influence of Game Based Learning in Informatics subjects on the Merdeka Curriculum in class VII-A as a control class and VII-I as an experimental class at SMP Negeri 5 Tangerang. The demands of learning programs urge teaching staff to always be innovative and creative in developing learning styles. However, in Informatics subjects, teachers only provide things that have been written in books and only focus on fulfilling the material without considering the learning output later even though in the independent curriculum, teachers are free to compile the material. The research aims to prove the hypothesis that motivation and learning achievement can be influenced by innovative learning models. This alternative applies an online game-based learning model with computational thinking material. The method used is an unequal control group experimental design. The use of motivation questionnaires and learning achievement tests are the instruments of this research. The research results show a significant increase in student learning motivation as well as student learning achievement because they have implemented the presentation of game-based learning methods for research classes in Informatics subjects